Impact of the Uruguay Round on tariff escalation in agricultural products - Lindland, Jostein (FAO RomeIT, 1997)
Examines the impact of the Uruguay Round on tariff escalation in three major agricultural markets viz. the European Union, Japan and the United States of America. Covers 276 different agricultural processed commodities.